The crystal structure of the co-crystal 1,4-dioxane–4,6-bis(nitroimino)-1,3,5-triazinan-2-one(2/1), C11H19N7O9 - Guannan Zhao; Tong Zhang; Jun Chen; Hongxia Pan; LiZhen Chen; Jianlong Wang (Zeitschrift für Kristallographie - New Crystal Structures)
C11H19N7O9, orthorhombic, P212121 (no. 19), a = 6.2578(2) Å, b = 15.4188(5) Å, c = 17.6841(7) Å, V = 1706.30(1) Å3, Z = 4, Rgt(F) = 0.0428, wRref(F2) = 0.0972, T = 100 K.